PENGARUH STRATEGI PEMASARAN DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA CAFE DEBU SELATAN, DI PESISIR SELATAN - Yanti, Yanti; Rahmanirwati, Dewi (Ensiklopedia of Journal, 2024)
This research aims to determine the influence of marketing strategy and brand equity on purchasing decisions at the South Debu Café, on the South Coast. This research is a quantitative research study, the sampling method uses incidental sampling techniques with a total of 100 respondents. The results of this research show that marketing strategy has a positive and significant effect on purchasing decisions so that the first hypothesis is accepted and then the second hypothesis that brand equity has a positive and significant effect on purchasing decisions.